The Relationship between Exclusive Breastfeeding and Stunting Incidents in Toddlers in the Working Area of the UPT Health Center Susut I Bangli - Muniari, Ni Ketut; Aswitami, Ni Gusti Ayu Pramita; Mastiningsih, Putu (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2022)
Stunting affects the growth and development of the brain. The problem of stunting occurs starting from the womb and will only be seen when the child is two years old. Stunting can be prevented by several things such as exclusive breastfeeding, providing nutritious food according to the needs of the child's body, implementing and getting used to clean living behaviors, and doing physical activity. The purpose of this study was to determine the relationship between exclusive breastfeeding and stunting in toddlers. 24-59 Months in the Working Area of UPT Puskesmas Susut I Bangli. The research conducted was a retrospective analytic research with a cross-sectional study design that emphasized the measurement/observation of independent and dependent variable data only once, at one time. The selection of the sample in this study is using a total sampling technique. The sample of this study were 31 toddlers aged 24-59 months. The results of the analysis using the Fisher's Exact test showed that out of 31 mothers, it was shown that 23 respondents (95.8%) were not given exclusive breastfeeding and 23 respondents (95.8%) were of normal height and 1 respondent (6.2%) were given breast milk. Exclusively with short height 0 respondents (0.0%) and with normal height 7 respondents (100%). The results of the study were declared significant if p 0.05 and the statistical test results obtained p = 0.00